To solve the equation x + 8 = 10, we need to isolate x by subtracting 8 from both sides:
x + 8 - 8 = 10 - 8
x = 2
Therefore, the solution to the equation x + 8 = 10 is x = 2.
Graphically, the solution can be represented as a point on a number line at the position 2.
As for checking the solution, substituting x = 2 back into the original equation:
2 + 8 = 10
10 = 10
The equation is true, which confirms that x = 2 is the correct solution.
Solve the equation. Graph and check your solutions.
x+8=10
Question content area bottom
Part 1
Solve the equation for x. Select the correct choice below and, if necessary, fill in the answer box to complete your choice.
A.
x= enter your response here
(Type an integer or a simplified fraction. Use a comma to separate answers as needed.)
B.
There is no solution.
13 answers
−3x=−18
Question content area bottom
Part 1
Select the correct choice and, if necessary, fill in the answer box in your choice below.
A.
x= enter your response here
(Simplify your answer. Use a comma to separate answers as needed.)
B.
There is no solution.
Question content area bottom
Part 1
Select the correct choice and, if necessary, fill in the answer box in your choice below.
A.
x= enter your response here
(Simplify your answer. Use a comma to separate answers as needed.)
B.
There is no solution.
To solve the equation -3x = -18, we need to isolate x by dividing both sides of the equation by -3:
(-3x) / -3 = (-18) / -3
x = 6
Therefore, the solution to the equation -3x = -18 is x = 6.
There is a solution to the equation. Thus, the correct choice is A. x = 6.
(-3x) / -3 = (-18) / -3
x = 6
Therefore, the solution to the equation -3x = -18 is x = 6.
There is a solution to the equation. Thus, the correct choice is A. x = 6.
Question content area top
Part 1
Solve the equation.
12=m+8
Question content area bottom
Part 1
Select the correct choice and, if necessary, fill in the answer box in your choice below.
A.
m= enter your response here
(Simplify your answer. Use a comma to separate answers as needed.)
B.
There is no solution.
Part 1
Solve the equation.
12=m+8
Question content area bottom
Part 1
Select the correct choice and, if necessary, fill in the answer box in your choice below.
A.
m= enter your response here
(Simplify your answer. Use a comma to separate answers as needed.)
B.
There is no solution.
To solve the equation 12 = m + 8, we need to isolate m by subtracting 8 from both sides of the equation:
12 - 8 = m + 8 - 8
This simplifies to:
4 = m
Therefore, the solution to the equation is m = 4.
The correct choice is A. m = 4.
12 - 8 = m + 8 - 8
This simplifies to:
4 = m
Therefore, the solution to the equation is m = 4.
The correct choice is A. m = 4.
Solve the equation.
10=m+3
Question content area bottom
Part 1
Select the correct choice and, if necessary, fill in the answer box in your choice below.
A.
m= enter your response here
(Simplify your answer. Use a comma to separate answers as needed.)
B.
There is no solution.
10=m+3
Question content area bottom
Part 1
Select the correct choice and, if necessary, fill in the answer box in your choice below.
A.
m= enter your response here
(Simplify your answer. Use a comma to separate answers as needed.)
B.
There is no solution.
To solve the equation 10 = m + 3, we need to isolate m by subtracting 3 from both sides of the equation:
10 - 3 = m + 3 - 3
This simplifies to:
7 = m
Therefore, the solution to the equation is m = 7.
The correct choice is A. m = 7.
10 - 3 = m + 3 - 3
This simplifies to:
7 = m
Therefore, the solution to the equation is m = 7.
The correct choice is A. m = 7.
Solve the equation.
6x−9=24
6x−9=24
To solve the equation 6x - 9 = 24, we can isolate x by adding 9 to both sides of the equation:
6x - 9 + 9 = 24 + 9
This simplifies to:
6x = 33
Next, we can solve for x by dividing both sides of the equation by 6:
(6x)/6 = 33/6
This simplifies to:
x = 5.5
Therefore, the solution to the equation is x = 5.5.
6x - 9 + 9 = 24 + 9
This simplifies to:
6x = 33
Next, we can solve for x by dividing both sides of the equation by 6:
(6x)/6 = 33/6
This simplifies to:
x = 5.5
Therefore, the solution to the equation is x = 5.5.
4|x-6|=28
To solve the equation 4|x - 6| = 28, we need to consider two cases: when the expression inside the absolute value is positive and when it is negative.
Case 1: When x - 6 is positive.
In this case, we can remove the absolute value and rewrite the equation as:
4(x - 6) = 28
Simplifying:
4x - 24 = 28
Adding 24 to both sides:
4x = 52
Dividing by 4:
x = 13
So one solution is x = 13.
Case 2: When x - 6 is negative.
In this case, we need to negate the expression inside the absolute value and rewrite the equation as:
4(-x + 6) = 28
Simplifying:
-4x + 24 = 28
Subtracting 24 from both sides:
-4x = 4
Dividing by -4:
x = -1
So another solution is x = -1.
Therefore, the equation 4|x - 6| = 28 has two solutions: x = 13 and x = -1.
Case 1: When x - 6 is positive.
In this case, we can remove the absolute value and rewrite the equation as:
4(x - 6) = 28
Simplifying:
4x - 24 = 28
Adding 24 to both sides:
4x = 52
Dividing by 4:
x = 13
So one solution is x = 13.
Case 2: When x - 6 is negative.
In this case, we need to negate the expression inside the absolute value and rewrite the equation as:
4(-x + 6) = 28
Simplifying:
-4x + 24 = 28
Subtracting 24 from both sides:
-4x = 4
Dividing by -4:
x = -1
So another solution is x = -1.
Therefore, the equation 4|x - 6| = 28 has two solutions: x = 13 and x = -1.
equation.
10x−7−15=1
10x−7−15=1
To solve the equation 10x - 7 - 15 = 1, we can combine like terms on the left side of the equation:
10x - 22 = 1
Next, we can isolate x by adding 22 to both sides of the equation:
10x = 23
Finally, we can solve for x by dividing both sides of the equation by 10:
x = 23/10
x = 2.3
Therefore, the solution to the equation 10x - 7 - 15 = 1 is x = 2.3.
10x - 22 = 1
Next, we can isolate x by adding 22 to both sides of the equation:
10x = 23
Finally, we can solve for x by dividing both sides of the equation by 10:
x = 23/10
x = 2.3
Therefore, the solution to the equation 10x - 7 - 15 = 1 is x = 2.3.